X^4-y^4 ------------------------ - 2y; x^3+yx^2-xy^2-y^3 упростите выражение

X^4-y^4 ------------------------ - 2y; x^3+yx^2-xy^2-y^3 упростите выражение
Гость
Ответ(ы) на вопрос:
Гость
x^4 - y^4 = (x^2 - y^2)(x^2 + y^2) x^3 + yx^2 - xy^2 - y^3 = x^2*(x + y) - y^2*(x + y) = (x + y)(x^2 - y^2) Сокращаем x^2 - y^2, остается [latex] \frac{x^2+y^2}{x+y} -2y= \frac{x^2+y^2-2y(x+y)}{x+y}= \frac{x^2+y^2-2xy-2y^2}{x+y} = [/latex] [latex]= \frac{x^2-2xy-y^2}{x+y}[/latex]
Не нашли ответ?
Ответить на вопрос
Похожие вопросы